Nasopharyngeal Colonization and levofloxacin Susceptibility of Streptococcus pneumoniae among Healthcare Workers in a Teaching Hospital in Tehran, Iran - Samadpanah, Maryam; Gachkar, Latif; Salarian, Sara; Hadavand, Fahimeh (Novelty in Biomedicine, 2020)
Background: Streptococcus pneumoniae commonly asymptomatically colonizes the human upper respiratory tract and the carriage rate varies between geographical regions. The colonized individuals are not only at risk of infections but also can be a source of transmission of the pathogen. The risk of the droplet or airborne transmission of pneumococcal strains healthcare workers is considerable. The current study aimed to determine the extent of nasopharyngeal colonization with S. pneumoniae and their levofloxacin susceptibility at a tertiary hospital in Tehran, Iran. Materials and Methods: During a six-month period, the nasopharyngeal swab samples collected from 300 volunteer healthcare workers of Imam Hossein Hospital. Samples screened for S. pneumoniae using standard conventional biochemical methods. The minimum inhibitory concentration (MIC) of levofloxacin was determined using a commercially available strip antibiotic test according to the clinical laboratory standards institute (CLSI) guidelines. Results: A total of 19 (6.3%) enrolled healthcare workers were colonized with S. pneumoniae. Amongst the enrolled volunteers, nurses had a higher rate of pneumococcal colonization (47.3%) followed by interns (21%) and laboratory workers (15.8%). Our analysis revealed that there was a significant correlation between smoking and pneumococcal colonization. The antimicrobial susceptibility testing showed that all of the isolates were susceptible to levofloxacin (MIC≤2 μg/ml). Conclusion: This low rate of pneumococcal colonization amongst healthcare professionals may be attributed to the low risk of horizontal transmission of severe pneumococcal infections in the hospital. Additionally, our findings indicated that levofloxacin was an effective antimicrobial agent for the treatment of pneumococcal infections.